Carbon‐Free O2 Cathode with Three‐Dimensional Ultralight Nickel Foam‐Supported Ruthenium Electrocatalysts for Li–O2 Batteries. Issue 13 (18th May 2017) - Liu, Ziqiang; Feng, Ningning; Shen, Zihan; Li, Fujun; He, Ping; Zhang, Huigang; Zhou, Haoshen
Abstract: A new carbon‐ and binder‐free O2 cathode was fabricated by electroplating Ru‐nanoparticle‐coated ultralight Ni foam, which has good electron‐conducting and electrocatalytic properties. This all‐metal monolithic structure was able to suppress CO2 evolution and provided 306 times higher capacity than commercial Ni foam‐based O2 cathodes. Abstract : That′s so metal : A new carbon‐ and binder‐free O2 cathode is fabricated by electroplating Ru‐nanoparticle‐coated ultralight Ni foam, which has good electron‐conducting and electrocatalytic properties. This all‐metal monolithic structure suppresses CO2 evolution and provides 306 times higher capacity than commercial Ni foam‐based O2 cathodes.